Negative differential resistance and switching behavior in single wall bamboo-shape carbon nanotubes based molecular device: A first-principles study nanoscale device design. (July 2017) - Kumar, Maneesh
Graphical abstract: Utilizing first principles density functional theory coupled with nonequilibrium Green's function, the transport properties of molecular device based on single wall bamboo-shape carbon nanotubes were explored theoretically. Highlights: Transport properties of single wall bamboo-shape carbon nanotubes are examined for the first time in a theoretical manner. Excellent negative differential resistance (NDR) behavior observed in case of single wall bamboo-shape carbon nanotubes. Very High peak to valley ratio are observed. Unique properties of BS-SWCNTs are attractive to potential application for future nano-circuit design. Abstract: By using the first-principles density functional theory and a nonequilibrium Green's function, the quantum electronic transport properties of single wall bamboo-shape carbon nanotubes created by partitioning in C(12, 0) zigzag single wall carbon nanotubes based molecular devices are investigated. In the present work, we designed and simulated C(12, 0) bamboo-shape single wall carbon nanotubes (BS-SWCNTs) by connecting the coronene (C24H12) molecule as interface of two pure zigzag C(12, 0) nanotubes by chemical bonds and interface regions, thus obtained six pentagons and six hexagons on both sides of the tube. We observed that this BS-SWCNTs device exhibits the negative differential resistance (NDR) with certain bias voltage 1.1 V. The current voltage characteristics of the BS-SWCNTs show a switching behavior at bias region 1.1–1.6 V and very high peak-to-valley current ratio of the order of 10 6 . A detailed analysis of the origin of NDR was carried out with transmission pathways, MPSH with various external bias voltages.